Analyzing the impact of energy consumption and income inequality on environmental degradation in Nigeria - Ekemezie, Ekene; Reuben, Okafor (CV. Kalimasada Group, 2025)
Environmental degradation has become a pressing global concern, with its effects particularly severe in developing economies such as Nigeria. As nations strive for economic growth and improved living standards, the resulting pressure on natural resources and the environment often goes unchecked. The study employed the Dynamic Ordinary Least Squares (DOLS) method, preferred over Ordinary Least Squares (OLS) and Fully Modified Ordinary Least Squares (FMOLS) due to its effectiveness in correcting for endogeneity, heteroskedasticity, and serial correlation through the inclusion of leads and lags. Additionally, the Autoregressive Distributed Lag (ARDL) approach was applied to analyze both short-run dynamics and long-run relationships. Data spanning 1990 to 2023 were sourced from WDI, WGI, and the Central Bank of Nigeria. The Results show that energy consumption and GDP per capita significantly increase CO₂ emissions, while government expenditure reduces them. Political stability also raises emissions, suggesting its role in promoting industrial growth. Income inequality lowers emissions but increases deforestation, likely due to unequal land access. For deforestation, energy consumption and government spending significantly reduce forest loss, while GDP per capita and political stability show insignificant effects. The model results are robust, with high explanatory power. The study highlighted the urgent need for equitable income distribution, cleaner energy adoption, and improved governance to advance environmental sustainability in Nigeria